2018
DOI: 10.1111/1462-2920.14069
|View full text |Cite
|
Sign up to set email alerts
|

Host genetic variation strongly influences the microbiome structure and function in fungal fruiting‐bodies

Abstract: Despite increasing knowledge on host-associated microbiomes, little is known about mechanisms underlying fungus-microbiome interactions. This study aimed to examine the relative importance of host genetic, geographic and environmental variations in structuring fungus-associated microbiomes. We analyzed the taxonomic composition and function of microbiomes inhabiting fungal fruiting-bodies in relation to host genetic variation, soil pH and geographic distance between samples. For this, we sequenced the metageno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…The composition of hyphae-associated bacterial communities may in part reflect differences in the composition of the hyphal cell walls and hyphal exudates (Rudnick et al, 2015), which would be expected to differ increasingly with a greater phylogenetic distance between fungal species. Other cases in which fungal fruiting-bodies were not directly in contact with soils showed that fungal phylogenetic variation was more important in structuring associated microbiomes than soil characteristics (Pent et al, 2018). Nevertheless, in the current study, the hyphae of individual Penicillium species represent unique niches for several specific hyphae-associated bacterial taxa, which could be due to the differences in fungal physiology and metabolic properties such as fungal exudate production, antibiotics production and even P solubilization capacity.…”
Section: Discussionmentioning
confidence: 52%
“…The composition of hyphae-associated bacterial communities may in part reflect differences in the composition of the hyphal cell walls and hyphal exudates (Rudnick et al, 2015), which would be expected to differ increasingly with a greater phylogenetic distance between fungal species. Other cases in which fungal fruiting-bodies were not directly in contact with soils showed that fungal phylogenetic variation was more important in structuring associated microbiomes than soil characteristics (Pent et al, 2018). Nevertheless, in the current study, the hyphae of individual Penicillium species represent unique niches for several specific hyphae-associated bacterial taxa, which could be due to the differences in fungal physiology and metabolic properties such as fungal exudate production, antibiotics production and even P solubilization capacity.…”
Section: Discussionmentioning
confidence: 52%
“…Host-associated microbiomes are important for the nutrition and health of their hosts: plants, animals, and macrofungi are extensively colonized by microorganisms that play key roles in their life cycles (Berg et al, 2014; Bahrndorff et al, 2016; Webster and Thomas, 2016; Pent et al, 2018). Studies on animals and plants have revealed that host identity, genotype, and environmental variables all contribute to shaping the microbial communities colonizing eukaryotic tissues (Bulgarelli et al, 2012; Lundberg et al, 2012; Bouffaud et al, 2014; Hacquard et al, 2015; Glynou et al, 2016), but the relative importance of each factor varies depending on the host and on the type of environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the factors that drive the assembly of these communities are poorly documented. A recent study on the microbiome structure of the epigeous fruiting bodies of the saprophytic fungus Marasmius oreades revealed that host genetic differences could be responsible for 25% of bacterial community structure variation (Pent et al, 2018). The authors thus proposed that, similarly to what’s known for animals and plants, host genetics could be an important driver of the structure and function of the microbiome of fungal fruiting bodies (Bulgarelli et al, 2012; Chaston et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond arthropods, fungal fruiting bodies sustain a wide range of other taxa-in particular among microscopic organisms (Gams, Diederich, & Põldmaa, 2004;Pent, Põldmaa, & Bahram, 2017). Parasitic and decomposing fungi thrive on fruiting bodies, and so do bacteria of multiple orders and phyla (Gams et al, 2004;Pent et al, 2017Pent et al, , 2018.…”
mentioning
confidence: 99%